Development of a single, practical measure of surgical site infection (SSI) for patient report or observer completion. Issue 4 (July 2017) - Macefield, Rhiannon C; Reeves, Barnaby C; Milne, Thomas K; Nicholson, Alexandra; Blencowe, Natalie S; Calvert, Melanie; Avery, Kerry NL; Messenger, David E; Bamford, Richard; Pinkney, Thomas D; Blazeby, Jane M
Background: Surgical site infections (SSIs) are the third most common hospital-associated infection and can lead to significant patient morbidity and healthcare costs. Identification of SSIs is key to surveillance and research but reliable assessment is challenging, particularly after hospital discharge when most SSIs present. Existing SSI measurement tools have limitations and their suitability for post-discharge surveillance is uncertain. Aims: This study aimed to develop a single measure to identify SSI after hospital discharge, suitable for patient or observer completion. Methods: A three-phase mixed methods study was undertaken: Phase 1, an analysis of existing tools and semi-structured interviews with patients and professionals to establish the content of the measure; Phase 2, development of questionnaire items suitable for patients and professionals; Phase 3, pre-testing the single measure to assess acceptability and understanding to both stakeholder groups. Interviews and pre-testing took place over 12 months in 2014–2015 with patients and professionals from five specialties recruited from two UK hospital Trusts. Findings: Analyses of existing tools and interviews identified 19 important domains for assessing SSIs. Domains were developed into provisional questionnaire items. Pre-testing and iterative revision resulted in a final version with 16 items that were understood and easily completed by patients and observers (healthcare professionals). Conclusion: A single patient and observer measure for post-discharge SSI assessment has been developed. Further testing of the validity, reliability and accuracy of the measure is underway.